Combustion of solid fuel in a hybrid porous reactor - Jovicic, Vojislav; Fedorova, Nataliia; Zbogar-Rasic, Ana; Makongue Nloka, Daniel Ernest Gustave; Reichert, Fernando; Delgado, Antonio (Energy Procedia, 2017)
One of the most significant human-made methane emission sources is the municipal solid waste (MSW), deposited on sanitary landfills and open dumps [1,2]. Within this work, an alternative MSW treatment concept is presented, which could provide a relatively clean waste/biomass-to-energy transformation. The proposed procedure comprises of a combustion and a gasification (or pyrolysis) step, which are consecutively taking place in a two-stage hybrid porous reactor system. The core of the system are two packed bed reactors, in which solid fuel (waste or biomass) is mixed with inert ceramic particles of similar size. This paper overviews the initial experimental investigation of the combustion step of a hybrid mixture, composed of wood pellets (fuel) and alumina balls (inert ceramic particles) in a 250 mm-high batch reactor. The temperature profile along the reactor, the concentration of CO and the flame front propagation velocity were measured as a function of the ceramic particle size (11 and 20 mm), the inert-to-fuel mass ratio (0:1, 2:1, 3:1) and the airflow rate (30, 42, 60 l/min). Experiments indicate that an increase of the mass ratio of inert-to-fuel material and a decrease of the inert ceramic particles size lead to a decrease of the maximum temperature of the packed hybrid bed. Measured CO concentrations showed strong dependence on the inert ceramic particle size, i.e. the particle size reduction from 20 to 11 mm resulted in a significant reduction of CO-emission peaks. The maximum flame front propagation velocity of 0.2 mm/sec was detected for the airflow of 42 l/min, the particle size of 20 mm and the mass ratio of 3:1.
UnivIS-Import:2018-09-11:Pub.2017.tech.ITC.stmmec.combus
Keywords: allothermal gasification; Combustion; hybrid filtration combustion; MSW; packed bed

Degradation of Low Concentrated Perfluorinated Compounds (PFCs) from Water Samples Using Non-Thermal Atmospheric Plasma (NTAP) - Jovicic, Vojislav; Khan, Muhammad Jehanzaib; Zbogar-Rasic, Ana; Fedorova, Nataliia; Poser, Alexander; Swoboda, Peter; Delgado, Antonio (Energies, 2018)
Perfluorinated compounds (PFCs) are manmade chemicals, containing the covalent C-F bond, which is among the strongest chemical bonds known to organic chemistry. Abundant use of these chemicals contaminates air, water, and soil around the world. Despite recent initiatives and legal regulations set to reduce their omnipresence, conventional water purification processes are either inefficient or very expensive, especially for low PFC contamination levels. This research is focused on the non-thermal atmospheric plasma (NTAP) decomposition of very low concentrations (<1 µg/L) of PFCs (especially perfluorooctanoic acid (PFOA) and perfluorooctanesulfonate (PFOS)), present in the wastewater produced during the process of PFCs removal from contaminated soil. The efficiency of the decomposition process was investigated for air, oxygen, and nitrogen plasma, with exposure times of 1–10 min and different plasma nozzle- and reactor sizes. Experiments demonstrated that the NTAP treatment is an efficient alternative method for degradation of more than 50% of the initial PFC concentration in the water samples, in less than 200 s. The final concentration of PFC showed strong dependency on the tested parameters. The treatment effect showed to be strongly non-linear with time, followed by the reduction of the pH-value of the treated sample, which might present a limiting factor for further PFC decompositio
UnivIS-Import:2018-09-11:Pub.2018.tech.ITC.stmmec.degrad
Keywords: Non-thermal atmospheric plasma; Perfluorinated compound (PFC) removal; Wastewater treatment

Effect of Steam Flow Rate and Storage Period of Superhydrophobic-Coated Surfaces on Condensation Heat Flux and Wettability - Fedorova, Nataliia; Lindner, Christian; Prado, Lucia; Jovicic, Vojislav; Zbogar-Rasic, Ana; Virtanen, Sannakaisa; Delgado, Antonio (Multimodal Technologies and Interaction, 2021)
The jumping-droplet phenomenon occurring on superhydrophobic (SHPhob) surfaces under special conditions may be beneficial for numerous systems using condensation, due to the reported increased heat transfer coefficients. One technique to create a SHPhob surface is coating, which can be applied to larger areas of existing elements. However, challenges are associated with coating stability and the realization of continuous dropwise condensation. This research examined the condensation of steam at different flow rates (2, 4 and 6 g/min) and its influence on heat flux and water contact angles on the SHPhob spray-coated aluminum samples. Special emphasis on the impact of time was addressed through a series of one and five-hour condensation experiments on the samples with different storage periods (coated either one year ago or shortly before testing). Over the experimental series at a higher steam flow rate (6 g/min), heat flux decreased by 20% through the old-coated samples and water contact angles transferred from the superhydrophobic (147°) to hydrophobic (125°) region. This can be attributed to the joint effects of the partial coating washout and the adsorption of the condensed water within the porous structures of the coating during steam condensation. The new-coated samples could sustain more than fifty hours of condensation, keeping the same heat fluxes and SHPhob characteristics.
Keywords: condensation heat transfer; steam flow rate; superhydrophobicity; coating; stability; contact angle

Experimental and numerical analysis of the heat transfer in a packed bed exposed to the high thermal radiation flux - Ruiz, Gustavo; Ripoll, Nicolás; Fedorova, Nataliia; Zbogar-Rasic, Ana; Jovicic, Vojislav; Delgado, Antonio; Toledo, Mario (International Journal of Heat and Mass Transfer, 2019)
This paper investigates temperature profiles and heat fluxes in a packed bed heated by radiation that simulates solar energy flux. For this purpose, the discrete element method (DEM) was used along a heat transfer model (conduction and radiation mechanism). Short-range model is proposed for considering thermal radiation in a discrete elements system, which represents an easy-to-implement and low-computational-cost alternative. As results of the simulations, thermal profiles through the packed bed were obtained, as well as the accompanying heat flux. Experiments were performed in a packed bed of inert ceramic particles (alumina spheres). A radiant porous burner was placed at the bottom of the packed bed to simulate an imposed concentrated solar heat flux. Numerical results show good agreement with experimental data. In addition, the thermal profiles, obtained by the heat transfer model in DEM, were compared with the results obtained by discretizing the conservation of energy equation of the solid phase using finite differences, showing a correlation between the power and temperatures reached. It is concluded that the radiation model proposed provides the basis to continue with the study of granular materials at high temperature, where radiation is the dominant mechanism</a

Experimental Investigation of Solid Fuel Combustion Process in a Hybrid Porous Reactor - Jovicic, Vojislav; Fedorova, Nataliia; Zbogar-Rasic, Ana; Toledo Torres, Mario; Delgado, Antonio (Journal of Energy and Power Engineering, 2017)
One of the most significant human-made methane emission sources is the MSW (municipal solid waste), deposited on sanitary landfills and open dumps. Within this work, an alternative MSW treatment concept is presented, which could provide a relatively clean waste/biomass-to-energy transformation. The proposed procedure comprises of a combustion and a gasification (or pyrolysis) step, which are consecutively taking place in a two-stage hybrid porous reactor system. The core of the system is two packed bed reactors, in which solid fuel (waste or biomass) is mixed with inert ceramic particles of similar size. This paper overviews the initial experimental investigation of the combustion step of a hybrid mixture, composed of wood pellets (fuel) and alumina balls (inert ceramic particles) in a 250 mm-high batch reactor. The temperature profile along the reactor, the concentration of CO and the flame front propagation velocity were measured as a function of the ceramic particle size (11 and 20 mm), the inert-to-fuel mass ratio (0:1, 2:1, 3:1) and the airflow rate (30, 42, 60 l/min). Experiments indicate that an increase of the mass ratio of inert-to-fuel material and a decrease of the inert ceramic particles size lead to a decrease of the maximum temperature of the packed hybrid bed. Measured CO concentrations showed strong dependence on the inert ceramic particle size, i.e. the particle size reduction from 20 to 11 mm resulted in a significant reduction of CO-emission peaks. The maximum flame front propagation velocity of 0.2 mm/sec was detected for the airflow of 42 l/min, the particle size of 20 mm and the mass ratio of 3:1.
UnivIS-Import:2018-09-11:Pub.2017.tech.ITC.stmmec.experi_8
Keywords: Combustion; allothermal gasification; MSW; hybrid filtration combustion; packed bed

Experimental investigation of the gravity influence on the condensation behaviour on Al and PTFE-samples - Fedorova, Nataliia; Macher, Philipp; Jovicic, Vojislav; Zbogar-Rasic, Ana; Delgado, Antonio (Proceedings der 27. GALA-Fachtagung "Experimentelle Strömungsmechanik", 2019)
The condensation heat transfer takes place in numerous industrial processes. The presented work was motivated by the possibility to increase the energy efficiency of industrial processes through the condensation of water vapour from flue gases (FG). It is especially relevant for such industries, like baking, textile, pulp and paper, drying, etc., where the FG at the end of the process is rich in water vapour (up to 90%vol). This FG is generally composed of non-condensable gas (mostly dry air) and condensable gas (mostly water vapour). Its thermal energy (sensible and latent) can be recovered, thus increasing the overall process efficiency. The heat transfer efficiency plays an important role in the condensation process and is strongly influenced by the condensation type. The dropwise condensation exhibits the increased heat transfer coefficient by up to one order of magnitude, comparing to the filmwise condensation. Therefore, the research interest lies in the investigation of methods, prioritizing the dropwise condensation on solid surfaces. One of the decisive mechanisms for the in-creased heat transfer coefficient and condensation rate is the cyclical sequence of droplet formation, growth and drainage. Among others, these are initiated by the surface properties and gravitational force. In order to investigate the influence of gravity on the surface condensation behaviour, the experimental investigation was done for a variable tilt angle of 0, 30, 60 and 75° relative to the horizontal, using two different sample materials (Aluminium and PTFE-Teflon® discs 60 x 3 mm). The reaction chamber was filled with ambient air and kept at 50°C. Simultaneously, the sample was cooled with air and the water vapour was gradually injected inside the chamber. The condensation on the sample was recorded by the HD camera with 180mm macro lens. The pressure and temperature profiles along the reactor were continuously recorded. The condensation process ran two times faster for the inclination angle of 75° compared to 0° in case of the Al-sample. Since the tilt angle induces the natural convection inside the reaction chamber, the vertical temperature gradient decreased with increasing the inclination angle from 0 to 75° (by 40% for the Al-sample; by 20% for the PTFE-sample). Experimental data indicate that gravity reduces the critical droplet size for drainage (from around 4 to 2mm for both samples) and facilitates coalescence effects. This results in an accelerated cycle of nucleation, droplet growth and drainage.
Keywords: Surface condensation; droplet formation; influence of gravity; Aluminium; PTFE (Teflon®)

Impact of non-thermal plasma on the abatement of Perfluorinated compounds present in minute quantities in water effluents - Khan, Muhammad Jehanzaib; Jovicic, Vojislav; Zbogar-Rasic, Ana; Fedorova, Nataliia; Poser, Alexander; Swoboda, Peter; Delgado, Antonio (Proceedings der 27. GALA-Fachtagung "Experimentelle Strömungsmechanik", 2019)
Based on the strongest C-F bonds backbone, Perfluorinated compounds (PFCs) are manmade chemicals that are omnipresent due to their immense use for the production of various products. Currently, these are also addressed as global contaminants, and are present on the word market since middle of the 20 th century. Non biodegradability and high half-life times generate serious adverse effects on humans and wild life. This calls for remediation. Updated lifetime health advisory, and water quality standards have been issued for PFCs by different US and European environmental agencies, but the conventional techniques for remediation are either inefficient, or turn out to be uneconomic, especially dealing with extremely minute quantities present in effluents. The present study copes with the reduction/removal of low concentrated (<1 μg/l) PFCs from waste water, using non-thermal atmospheric plasma (NTAP). The research experimentally investigates influences of different parameters e.g. plasma gases (air, O2 and N2), treatment times (up to 10 min.) and nozzle/reactor sizes on the reduction of PFC concentrations. Promising results were obtained with NTAP exposure on the PFC concentration levels. In less than 200 seconds, the concentration thresholds of below 50% of initial PFCs concentration was reached in most of the tests within the shown experimental setup. The final concentration of PFCs was strongly dependent on the tested parameters. The decreasing pH value of the water was found to be a limiting factor for the lower PFCs concentration threshol
Keywords: Non-thermal atmospheric plasma; PFC removal; waste water treatment

Investigation of the Concepts to Increase the Dew Point Temperature for Thermal Energy Recovery from Flue Gas, Using Aspen® - Fedorova, Nataliia; Aziziyanesfahani, Pegah; Jovicic, Vojislav; Zbogar-Rasic, Ana; Khan, Muhammad Jehanzaib; Delgado, Antonio (Energies, 2019)
Thermal energy of flue gases (FG) dissipating from industrial facilities into the environment, constitute around 20% of the total dissipated thermal energy. Being part of the FG, water vapour carries thermal energy out of the system in the form of the latent heat, which can be recovered by condensation, thus increasing the overall efficiency of an industrial process. The limiting factor in this case is the low dew point temperature (usually 40–60 °C) of the water vapour in the FG. The increase of the dew point temperature can be achieved by increasing the water content or pressure. Taking these measures as a basis, the presented work investigated the following concepts for increasing the dew point temperature: humidification of the flue gas using water, humidification using steam, compression of the FG and usage of the steam ejector. Modelling of these concepts was performed using the commercial software Aspen®. The humidification of the FG using water resulted in the negligible increase in the dew point (3 °C). Using steam humidification the temperatures of up to 92 °C were reached, while the use of steam ejector led to few degrees higher dew point temperatures. However, both concepts proved to be energy demanding, due to the energy requirements for the steam generation. The FG compression enabled the achievement of a 97 °C dew point temperature, being both energy-efficient and exhibiting the lowest energy cos
Keywords: thermal energy recovery; flue gas; dew point temperature; condensation; Aspen®

Static wettability of differently mechanically treated and amphiphobic-coated aluminium surfaces - Fedorova, Nataliia; Ottinger, Bettina; Jovicic, Vojislav; Zbogar-Rasic, Ana; Delgado, Antonio; Virtanen, Sannakaisa (Materials, 2020)
Wettability, roughness and surface treatmentmethods are essential for themajority of practical applications, where liquid-solid surface interactions take place. The present study experimentally investigated the influence of different mechanical surface treatment methods on the static wettability of uncoated and amphiphobic-coated aluminium alloy (AlMg3) samples, specially focusing on the interaction between surface finishing and coating. Five different surfaces were prepared: as-received substrate, polished, sandpapered, fleece-abraded and sandblasted. After characterisation, the samples were spray-coated using an amphiphobic coating. The characterisation of the uncoated and coated samples involved measurements of the roughness parameters and the apparent contact angles of demineralized water and rapeseed oil. The coating was initially characterised regarding its adhesion to the sample and elevated temperature stability. The applied surface treatments resulted in the scattered sample roughness in the range of Sa = 0.3-15.8 μm, water contact angles of θap,w = 78°-106° and extremely low oil contact angles. Coating the samples more than doubled the surface roughness to Sa = 13.3-29 μm, whereas the initial surface treatment properties (structure, anisotropy, etc.) were entirely repressed by the coating properties. Coating led the water contact angles to increase to θap,w_coated = 162°-173° and even more pronounced oil contact angles to increase to θap,o_coated = 139°-150°, classifying the surfaces as superhydrophobic and oleophobic.
CRIS-Team Scopus Importer:2020-06-02
Keywords: Amphiphobic; Contact angle; Roughness; Superhydrophobic; Surface treatment; Wettability

Syngas production from waste tires using a hybrid filtration reactor under different gasifier agents - Toledo Torres, Mario; Ripoll, Nicolás; Céspedes, José; Zbogar-Rasic, Ana; Fedorova, Nataliia; Jovicic, Vojislav; Delgado, Antonio (Energy Conversion and Management, 2018)
This paper investigates the syngas production in a hybrid filtration reactor composed of aleatory waste tires particles and alumina spheres. Parameters as reaction wave temperature, propagation rate and gaseous and solid emissions products were measured as a function of gasifier agents (air and steam) and natural gas presence. Hydrogen and carbon monoxide concentrations in the reaction products were determined by gas chromatography and solid emissions by X-ray spectrometry. Downstream reaction zone propagation was observed in all experiments yielding high reaction temperature (1,100–1,500 K) responsible of: (1) generating H2 and CO as main products of the process for different gasifier agents and natural gas presence, and (2) decreased solid particles emissions in comparison with temperatures below 1,100 K. X-ray spectrometry with total reflection was able to detect peaks of Zn and Fe, thought to originate from waste tires particles as well as from reactoŕs insulation material. It was detected that pure air had the best performance as a gasifier agen
Keywords: Hydrogen; Hybrid filtration reactor; Tires valorization; Solid emissions